Enhancing self-determination to optimize career decision-making - Sagala, Selfi Priska; Wibowo, Doddy Hendro (JURNAL SPIRITS, 2023)
This researcher is important for teenagers who still have anxiety about their desired career because one of the factors in making career decisions is self-determination which can help teenagers in making career decisions because self-determination is the drive that exists within an individual to achieve life goals, especially career. From the explanation above, the aim of this research is to answer the existence of a relationship between self-determination and career decision making among teenagers in Salatiga City Orphanage. The method used in this research uses quantitative methods with a quantitative correlational research design. The data collection technique used in this research was distributing psychological scales in the form of a physical questionnaire. The sampling technique used is nonprobability sampling with purposive sampling technique. The population of this study were teenagers in Salatiga City Orphanage with 105 subjects. The sampling technique used was purposive sampling. The research results showed a correlation of 0.523 (p<0.05), which means there is a significant positive relationship between self-determination and career decision making among teenagers in Salatiga City Orphanage. So that teenagers who have good self-determination will find it easier to make career decisionsthat suit their abilities